Morocco’s Western Sahara Policy during the reign of Mohammed VI - Zhiwen, Liang (Kashere Journal of Politics and International Relations, 2024)
Disputes over land, territories and boundaries are historically contentious ones which most oftentimes lead to conflicts, clashes and war between two or more territories and it also determines the balance of power and nature of relationship between the disputing parties. History is replete with many instances/examples of territorial conflicts between nations. Therefore, Morocco-Western Sahara conflict is one that has threatened the regional peace, security and balance of power in the Northwestern region of Africa for over five decades since its emergence. There has been several attempts by both parties to the conflict and other international state and non-state actors towards proffering a lasting solution to this dispute. However, like most territorial disputes, there has been failure in finding a lasting solution to the conflict between both sides. With a special reference to Morocco’s Western Sahara policy during the reign of King Mohammed VI, this study revealed that the ascension of the new Monarch; Mohammed VI brought about dynamism in Morocco’s policy towards this contested territory. Furthermore, in this study, it is also revealed that King Mohammed VI maintained the hardline and assertive approach towards Western Sahara. Just like his predecessor and father: King Hassan II, Mohammed VI views the Western Sahara region as part of the historical Morocco Kingdom. Relying on secondary data/sources obtained from journals and scholarly articles on the subject, this study adopted a historical and narrative approach in reporting its findings, thereby contributing to the teeming body of literature on the subject under discourse.